Synthesis and characterisation of novel phosphonate-based linkers and metal-organic frameworks based on tetravalent metals - Steve Shearan (2022)
The interest in metal-organic frameworks (MOFs) has skyrocketed in the past two decades, owing mainly to their tunable structures and properties. The main approach for this thesis is to explore the synthesis of novel metal(IV) phosphonate frameworks, mainly based on zirconium(IV). Exploring the effect of linker geometry on the structure of MOFs, a series of non-linear linkers were synthesised and assessed on their effectiveness in forcing the structure away from the conventional pillared-layered structures observed in a large portion of metal phosphonate literature. The subsequent structures were then assessed for their suitability in applications such as carbon capture and photocatalysis. With the interest in crystallisation evident, an in-depth in situ XRD crystallisation study was also carried out on two existing Ce(IV)-based MOFs, one of which had been identified for its promising carbon capture properties, and was also subject to a scale-up study to assess the potential for commercial deployment.